The Roots of Secularism in Northern Cyprus and Turkeyâ€™s Ambition of Islamization - Riskiansyah Ramadhan (Ijtimā`iyya: Journal of Muslim Society Research, 2020)
The conquest of Cyprus by the Ottoman Empire in 1571 had an impact on the growing Muslim population there. However, the majority Muslim population does not make Northern Cyprus adopt Islam as the official religion of the country. This article aims to analyze the roots of secularism in Northern Cyprus, some of which are caused by British government policies, the rise of Kemalism, the emergence of Alevism and Linobambaki, and the repression of Sufi orders at the end of Ottoman rule. Besides, the political situation in Turkey turned out to have an impact on Northern Cyprus, where Turkey sought to implement the Islamization policy there.